Molecular structure, spectral, computational, IEFPCM investigation, and topological study on the biologically potent; cardiotonic drug 2-chloroquinolin-3-amine with structural optimization - A. Saral; R. Shahidha; M. Thirunavukkarasu; S. Muthu (Chemical Physics Impact, 2023)
The current study provides a detailed DFT analysis of the drug 2-Chloroquinolin-3-amine, which has biological potential as a cardiotonic (2CQ3A). The molecular structure is theoretically optimised using DFT with the basis set B3LYP/6–311++G(d,p), and parameters were measured .Potential energy distribution was used in Fourier transforms, IR, and Raman analysis. Different solvents underwent UV–Visible analysis, and the bandgap energy of the Frontier molecular orbital were compared. By using NBO and MEP studies in various solvents, the molecule's stability and reactivity were predicted using the IEFPCM methodology. The compound's non-linear optical behavior is demonstrated by NLO analysis in a variety of polar and non-polar solvents. AIM, ELF, LOL, and RDG were predicted by topological analysis. ADME properties and toxicity values are assigned to demonstrate the compound's biological activity. Cardiotonic activity by docking is analysed using molecular modeling techniques.